Formation of nanometer-sized Cu-Sn-Se particles in Cu2ZnSnSe4 thin-films and their effect on solar cell efficiency. (15th June 2017) - Schwarz, Torsten; Cojocaru-Mirédin, Oana; Mousel, Marina; Redinger, Alex; Raabe, Dierk; Choi, Pyuck-Pa
Abstract: Atom probe tomography and transmission electron microscopy are used to study the formation of nano-sized Cu-Sn-Se particles in Cu2 ZnSnSe4 thin-films. For a Cu-rich precursor, which was deposited at 320 °C under Cu- and Zn-rich growth conditions, Cu2-x Se grains at the surface are detected. During annealing the precursor at 500 °C in a SnSe + Se atmosphere most of the Cu2-x Se is transformed to Cu2 ZnSnSe4 via the consumption of excessive ZnSe and incorporation of Sn. However, atom probe tomography studies also reveal the formation of various nanometer-sized Cu-Sn-Se particles close to the CdS/Cu2 ZnSnSe4 interface. One of those particles has a composition close to the Cu2 SnSe3 compound. This phase has a smaller band gap than Cu2 ZnSnSe4 and is proposed to lead to a significant drop in the open-circuit voltage and could be the main cause for a detrimental p-n junction and the zero efficiency of the final device. Possible effects of the other phases on solar cell performance and formation mechanisms are discussed as well. Graphical abstract: Image 1